On-farm description and status of Nuer (Abigar) cattle breed in Gambella Regional State, Ethiopia - Minuye, N.; Abebe, G.; Dessie, Tadelle (Academic Journals, 2018)
This study was conducted in Gambella Regional State (GRS) in order to characterize the Abigar cattle breed phenotypically at its breeding tract.It was done purposively in four selected districts of the region using extensive field surveys, morphological measurements and focused group discussions on the origin, distribution, current status and future threats, production and reproduction characteristics of Abigar cattle at its production environment.By using semi-structured questionnaire, 160 cattle owners were interviewed and qualitative and quantitative data were recorded for mature 200 female and 100 male cattle.Milk yield monitoring of 95 lactating Abigar cows was assessed in and around Gambella district for three months long.The data were entered into Excel sheet and analyzed using SPSS (2007) software package.The study has shown that Abigar cattle are the most dominant both in the Nuer and Anywaa zones of the region.The breed possesses unique features that can be used in identifying the breed from other indigenous breeds.The breed has got large body size, long-curved horns, gray and white dominant coat colors as well as ease of management by all gender groups due to its recognized docile character.The average age at puberty, age at first calving and calving interval were found to be 36.2,42.5 and 14.1 months, respectively under extensive management.In addition, the breed has better production and reproduction capabilities despite the high heat load, recurrent drought and repeated disease prevalence in the region.However, a decreasing trend of the breed had been noticed in the studied areas in recent years mainly due to disease outbreaks and lack of medication, ethnic conflicts, cattle raiding and high expansion of commercial crop production.Thus, a well-coordinated and community driven participatory in situ conservation strategy has great significance to ensure the maintenance, future use and improvement of the breed for enhancement of food security of the pastoral and agro-pastoral communities in the region.